The Role Of Productive Waqf In Promoting Sustainable Economic Development In The Gontor Ecosystem - Rizqi Aulia, Putri Ayu; Triyawan, Andi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
This study examines the implementation and economic impact of productive waqf within the ecosystem of Pondok Modern Darussalam Gontor (PMDG), a waqf-based Islamic educational institution known for its financial independence and sustainability model. Using a qualitative descriptive approach with a case study design, data were collected through document analysis, institutional reports, field observations, and semi structured interviews with waqf administrators and business unit managers. The findings reveal that Gontor has developed an integrated productive waqf ecosystem that combines physical waqf assets, human resource waqf (waqf basyari), and diversified business units operating in agriculture, publishing, education, cooperatives, and retail sectors. This system generates stable revenue streams that support operational costs, educational subsidies, scholarships, and community empowerment programs. The study also shows that PMDG applies strong sharia-based governance principles transparency, accountability, and periodic internal audits which ensure the sustainability and efficiency of waqf management. Beyond institutional benefits, productive waqf at Gontor contributes to local economic development through job creation, micro-economic stimulation, and equitable welfare distribution. These findings demonstrate that productive waqf, when professionally managed, can function as a strategic instrument for sustainable economic development and serve as a replicable model for other Islamic educational institutions. The study recommends strengthening waqf literacy, enhancing nazhir capacity, and expanding digital-based waqf management to support broader national implementation